A flavin-inspired covalent organic framework for photocatalytic alcohol oxidation. Issue 45 (15th November 2021) - Trenker, Stefan; Grunenberg, Lars; Banerjee, Tanmay; Savasci, Gökcen; Poller, Laura M.; Muggli, Katharina I. M.; Haase, Frederik; Ochsenfeld, Christian; Lotsch, Bettina V.
Abstract : In this manuscript, we report the development of a novel alloxazine COF inspired by naturally occurring flavin cofactors for photoredox catalysis. Abstract : Covalent organic frameworks (COFs) offer a number of key properties that predestine them to be used as heterogeneous photocatalysts, including intrinsic porosity, long-range order, and light absorption. Since COFs can be constructed from a practically unlimited library of organic building blocks, these properties can be precisely tuned by choosing suitable linkers. Herein, we report the construction and use of a novel COF (FEAx-COF) photocatalyst, inspired by natural flavin cofactors. We show that the functionality of the alloxazine chromophore incorporated into the COF backbone is retained and study the effects of this heterogenization approach by comparison with similar molecular photocatalysts. We find that the integration of alloxazine chromophores into the framework significantly extends the absorption spectrum into the visible range, allowing for photocatalytic oxidation of benzylic alcohols to aldehydes even with low-energy visible light. In addition, the activity of the heterogeneous COF photocatalyst is less dependent on the chosen solvent, making it more versatile compared to molecular alloxazines. Finally, the use of oxygen as the terminal oxidant renders FEAx-COF a promising and "green" heterogeneous photocatalyst.